The hepatitis C treatment revolution: how to avoid Asia missing out - Nick Walsh; Nicolas Durier; Giten Khwairakpam; Annette H. Sohn; Ying-Ru Lo (Elsevier, 2015)
The Asia-Pacific region bears a high burden of hepatitis C virus (HCV) infections and the largest number of global deaths. Populations most at risk of infection and disease progression include people who inject drugs and those living with HIV. HCV treatment options have rapidly expanded in the past few years through the development of direct-acting antiviral (DAA) medicines, which can cure HCV in over 95% of cases, but are prohibitively expensive. While price is the major barrier to treatment access, voluntary licensing has resulted in limited availability of one DAA (sofosbuvir) through generic manufacturers in India. Regulatory barriers, such as the need for domestic clinical trials, cause further delays in local medicines approvals and access.Intensive advocacy by civil society in combination with mobilisation of global resources for HIV treatment were critical to achieving price reductions in HIV medicines in the early 2000s. While the current global economic situation is less conducive to substantial funding support for HCV treatment, community advocates are building awareness of the growing opportunities for HCV cure. Key immediate steps include the inclusion of DAAs in domestic essential medicines lists, as the World Health Organization has already done for globally, and fast-tracking domestic drug approvals to facilitate government-level price negotiations with originator and generic pharmaceutical companies. Urgent action by a broad range of stakeholders is needed to facilitate access to HCV treatment in order to ensure that the millions of people living with hepatitis C in the Asia-Pacific will not miss out on these life-saving treatments.